Formation of speech culture of primary schoolchildren by means of speech metaphoricity - Fatima Kaplanovna Urakova; Inna Vladimirovna Shcherbashina; Saida Nurbievna Pkhanaeva (Вестник Майкопского государственного технологического университета)
Modern education and upbringing is characterized by qualitatively new requirements imposed by educational standards, not only for the content of the educational process, but also for the development of students’ personal qualities. The implementation of these requirements occurs in the process of improving the speech culture of primary schoolchildren. Thus, the development of speech culture of students in general and its expressiveness, in particular, is becoming one of the urgent problems of modern language education. One of the means of forming the expressiveness of speech is its metaphor. The mastery of the metaphor by primary schoolchildren as a way of transferring the name of one object to another with any similar sign develops their imaginative thinking, expands their vocabulary, develops the ability to select words, makes speech more spatial and fulfilling. The relevance of the article is determined by the need to form the speech culture of primary school children on the basis of the metaphorical nature of speech and the lack of undeveloped relevant scientifically grounded learning systems that make it possible to put this provision into practice. The purpose of the article is to determine some theoretical provisions of the problem and to present a methodological system for the formation of the speech culture of primary schoolchildren on the basis of the metaphorical nature of speech. The research methods used are theoretical analysis, analysis of the products of students’ activity, fixation of the educational process, pedagogical experiment. The authors presented the following provisions: the concepts of «speech culture», «expressiveness of speech», «metaphor» have been clarified; the indicators of the formation of skills in the field of metaphorical speech in junior schoolchildren have been determined, a methodological system for the formation of speech culture based on the metaphoricity of speech has been developed, the effectiveness of the proposed methodological system has been experimentally proved. The conclusions: the problem of improving the speech culture of students and, in particular, its expressiveness on the basis of metaphor is quite wide and diverse. Knowledge in the field of metaphorical speech helps younger students to achieve a higher level of development of speech culture.